HUBUNGAN PERAN ORANGTUA TERHADAP SIKAP REMAJA DALAM PENCEGAHAN SEKS PRANIKAH - sri hazanah; Dwi Hendriani; Rivan Firdaus (MNJ (Mahakam Nursing Journal), 2019)
Adolescence is a period of transition between childhood and adulthood, experiencing changes in mental, emotional, social, physical, and sexual maturity. If there is no supervision, direction, guidance from the closest person such as parents, family, educators, there might be unexpected sexual deviations such as; premarital pregnancy and sex occur. The purpose of the study was to determine the relationship between the role of educators and parents on adolescent attitudes in preventing premarital sex in Balikpapan in 2017. Survey research methods with cross sectional design. Study sample 119 students of Balikpapan Health Vocational School aged 14-18 years, taking techniques using Random Sampling. Data research techniques using questionnaires with Linkert scale. Data analysis used univariate analysis with frequency distribution, bivariate analysis with chi square (x2) statistical test and multivariate logistic regression test with significance p <0.05. The results: the role of educators supports 68 (57.1%), the role of parents supports 72 (60.5%), and positive teen attitudes 62 (52.1%) there is a relationship between the role of educators on adolescent attitudes with values ​​(OR = 2.504, 95% CI (1.19 - 5.27) p value = 0.024), there is no relationship between parental role and adolescent attitudes with values ​​(OR = 2.185, 95% CI (1.03-4.62) and p value = 0.061). Strength regression test the relationship of the role of the parent value OR = (0.74) and the role of the educator OR = (0.57). Conclusion: the role of parents has no relationship but more dominant influence on changes in adolescent attitudes compared to the role of educators, it needs to be the attention of all parties because adolescents are a time to seek self-identity so that the environment is easily influenced. Suggestion: parents, educators and other parties (religion, government) pay more attention to adolescents to avoid premarital sex deviations.